Diethylcarbamazine Reduces Chronic Inflammation and Fibrosis in Carbon Tetrachloride- (CCl4-) Induced Liver Injury in Mice - Rocha, Sura Wanessa Santos; França, Maria Eduarda Rocha de; Rodrigues, Gabriel Barros; Barbosa, Karla Patrícia Sousa; Nunes, Ana Karolina Santana; Pastor, André Filipe; Oliveira, Anne Gabrielle Vasconcelos; Oliveira, Wilma Helena; Luna, Rayana Leal Almeida; Peixoto, Christina Alves (Mediators of Inflammation, 2014)
This study investigated the anti-inflammatory effects of DEC on the CCl4-induced hepatotoxicity in C57BL/6 mice. Chronic inflammation was induced by i.p. administration of CCl4 0.5 μL/g of body weight through two injections a week for 6 weeks. DEC (50 mg/kg) was administered by gavage for 12 days before finishing the CCl4 induction. Histological analyses of the DEC-treated group exhibited reduced inflammatory process and prevented liver necrosis and fibrosis. Immunohistochemical and immunofluorescence analyses of the DEC-treated group showed reduced COX-2, IL1β, MDA, TGF-β, and αSMA immunopositivity, besides exhibiting decreased IL1β, COX-2, NFκB, IFNγ, and TGFβ expressions in the western blot analysis. The DEC group enhanced significantly the IL-10 expression. The reduction of hepatic injury in the DEC-treated group was confirmed by the COX-2 and iNOS mRNA expression levels. Based on the results of the present study, DEC can be used as a potential anti-inflammatory drug for chronic hepatic inflammation.